SEMINAR DAN PELATIHAN TENTANG DAUR ULANG SAMPAH PLASTIK DI DUTASIA LEARNING TANGERANG - Wahyu Irawati; Georgine Gladis Paula Sulardi; Grace Charity Mary Cartir; Greisnaningsi Greisnaningsi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Plastic waste is a by-product of daily human activities which if not managed properly will cause environmental problems. Community Service is held at Dutasia learning, Jl. Gandasari No. 45, Gandasari, Jatiuwung Sub-district, Dumpit, Tangerang, Banten 15810. Analysis of the situation at Dutasia Learning shows that Dutasia residents have few limitations in their awareness of environmental care. Many residents, especially children, throw plastic in any place so that there are piles of plastic in several locations. This Community Service aims to conduct seminars and training on the role of plastic waste recycling in environmental conservation. The seminar was accompanied by training on how to make recycled plastic products into useful products. The event lasted for two hours and was attended by 35 residents of Dumpit Village consisting of teenagers and children. The results of this activity are in the form of products from training on making recycling in the form of plastic wallets and pencil cases from mineral water bottles. A total of 25 children managed to finish making pencil cases, three children completed plastic wallets, and the rest finished it at home. Through this PkM activity, it is hoped that Dutasia residents have new insights to use plastic as needed, reuse plastic that can still be used for other purposes, and make plastic waste recycling into useful products.Keywords: Recycling, environment, plastic, product, waste.